The Demographics of Expropriation Risk - Philipp Harms; Philipp an de Meulen (Swiss National Bank, Study Center Gerzensee, 2009)
It is often argued that capital should flow from aging industrialized economies to countries with fast-growing populations. However, institutional failures and the risk of expropriation substantially reduce developing economies' attractiveness for foreign investors. We analyze the influence of a country's demographic structure on international investment, using a political-economy model in which population growth potentially affects the risk of expropriation. We first explore how redistributive expropriation affects the welfare of different age groups and derive the government's incentive to expropriate. We then analyze how the relative size of different generations influences the feasible volume of foreign investment.
Keywords: F21; D78; J10; 330; International Investment; Political Economy; Demographics; Auslandsinvestition; Bevölkerungsstruktur; Enteignung; Investitionsrisiko; Wirtschaftswissenschaft; Theorie